Molecular Mechanism of Citrate Efflux by the Mitochondrial Citrate Transporter CT in Filamentous Fungus Mucor circinelloides WJ11 - Yang, Wu; Dong, Shiqi; Yang, Junhuan; Mohamed, Hassan; Shah, Aabid Manzoor; Nazir, Yusuf; Gao, Xiuzhen; Fan, Huirong; Song, Yuanda (Frontiers in Microbiology, 2021)
The mitochondrial citrate transporter (MCT) plays an important role in citrate efflux from the mitochondria in eukaryotes, and hence provides a direct correlation between carbohydrate metabolism and lipid synthesis. Our previous studies on transporters confirmed the presence of two MCTs (TCT and CT) in oleaginous Mucor circinelloides WJ11 associated with high lipid accumulation. However, the molecular mechanism of citrate efflux from the mitochondria by MCT in M. circinelloides is still unclear. To study the citrate transport mechanism of CT, the citrate transporter gene was expressed in Escherichia coli, and its product was purified. The citrate transport activity of the protein was studied in CT reconstituted liposomes. Our results showed high efficiency of CT for [14C] citrate/citrate exchange with Km 0.01 mM at 25°C. Besides citrate, other molecules such as oxaloacetate, malate, fumarate, succinate aconitate, oxoadipate, isocitrate, and glutamate also promotes citrate transport. In addition, the ct over-expression and knockout plasmids were constructed and transferred into M. circinelloides WJ11, and the mitochondria were isolated and the transport activity was studied. Our findings showed that in the presence of 10 mM malate, the mitochondria of ct-overexpressing transformant showed 51% increase in the efflux rate of [14C] citrate, whereas the mitochondria of the ct-knockout transformant showed 18% decrease in citrate efflux compared to the mitochondria of wild-type WJ11. This study provided the first mechanistic evidence of citrate efflux from the mitohondria by citrate transporter in oleaginous filamentous fungus M. circinelloides which is associated with high lipid accumulation.